1998
DOI: 10.1136/hrt.79.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pulmonary hypertension with the continuous infusion of a prostacyclin analogue, iloprost

Abstract: Objective-To compare prostacyclin with an analogue, iloprost, in treatment of severe pulmonary hypertension. Patients-Eight patients with severe pulmonary hypertension: primary in five, thromboembolic pulmonary hypertension in three. Methods-All patients underwent right heart catheterisation. Mean (SEM) right atrial pressure was 9.9 (2.2) mm Hg, mean pulmonary artery pressure 67.4 (3.0) mm Hg, cardiac index 1.75 (0.13) l/min/m 2 and mixed venous oxygen saturation 59.1(3.1)%. Continuous intravenous epoprostenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 16 publications
2
53
0
7
Order By: Relevance
“…Moreover, iloprost has a biphasic disposition, with longer half-lives of 3-4 and 30 min, in contrast to the half-life ofv5 min of epoprostenol [19]. In addition, much lower doses of iloprost are needed for a comparable haemodynamic effect [20].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, iloprost has a biphasic disposition, with longer half-lives of 3-4 and 30 min, in contrast to the half-life ofv5 min of epoprostenol [19]. In addition, much lower doses of iloprost are needed for a comparable haemodynamic effect [20].…”
Section: Discussionmentioning
confidence: 96%
“…It has a similar molecular structure to prostacyclin and works though prostacyclin receptors present on vascular endothelial cells. Iloprost is more stable than epoprostenol and can be stored at room temperature without needing protection from light [74]. It has a biological half-life of 20-30 min [77].…”
Section: Inhaled Prostacyclin Analoguementioning
confidence: 99%
“…Although inhaled iloprost, a stable synthetic analogue of prostacyclin, has been shown to be efficacious in improving haemodynamics and exercise capacity in pulmonary arterial hypertension patients [72][73][74][75][76], the clinical experience with children is extremely limited. It has a similar molecular structure to prostacyclin and works though prostacyclin receptors present on vascular endothelial cells.…”
Section: Inhaled Prostacyclin Analoguementioning
confidence: 99%
“…iloprost was effective in improving exercise capacity and pulmonary haemodynamics in PAH. However, these studies were limited in size (eight and 13 patients treated with iloprost [12,13], respectively) and included heterogeneous forms of pulmonary hypertension. Intravenous iloprost was never evaluated in a formal randomised placebocontrolled trial.…”
mentioning
confidence: 99%
“…Short-term open-label [12] and observational [13] studies suggested i.v. iloprost was effective in improving exercise capacity and pulmonary haemodynamics in PAH.…”
mentioning
confidence: 99%